Antecedents of Tawhidic Culture for Developing Sustainable Competitive Advantage Through a Strategic Approach - Budiyono, Rokhmad; Widodo, Widodo; Purwanto, Edy (IQTISHADIA, 2024)
This article aims to empirically prove a new theoretical approach developed to address the gap in prior research regarding the impact of organizational learning on sustainable competitive advantage from the perspective of a shared vision. It focuses on tawhidic culture that is aligned with the exploitation and exploration of knowledge. The design research was conducted by distributing a questionnaire to 117 respondents from 54 private universities in Central Java, Indonesia. The data obtained from the questionnaires was then processed using the structural equation modeling (SEM) technique. The research findings indicate that implementing tawhidic culture in a private university in Central Java has a positive impact towards sustainable competitive advantage. This impact occurs when tawhidic culture is effectively integrated into all aspects of the institution, including the development of a shared vision through a tawhidic culture, which positively influences the realization of sustainable competitive advantage. The positive influence of a tawhidic culture on enhancing sustainable competitive advantage is also evident when there is an increase in knowledge exploration. This article presents a novel research variable, tawhidic culture, which is constructed based on the integration of the resourcebased view (RBV) theory of strategic assets with the tahidic paradigm. This variable serves as a foundation for enhancing sustainable competitive advantage